The Potential Development of Community Based Tourism at Ambengan Village, Buleleng Regency, Bali - Komang Trisna Pratiwi Arcana; Kadek Wiweka (Journal of Business on Hospitality and Tourism, 2015)
This study discussed the concept of sustainable tourism development which used participation-based of local communities in northern Bali, especially in Ambengan village in accordance with the concept of community-based tourism (CBT). To achieve the objectives of the research, this study has identified potential Ambengan village as a community-based tourism products, which consists of; attraction, accessibilities, amenities, ancillaries, activity, and community involvement. Followed by observation method, which were analyzed by using a life-cycle model of destination, it is known that Ambengan village as a tourist destination are in phase with the attitude of the community involvement is at euphoria. However, for determining the form of community participation, this study using in-depth interviews were subsequently combined with secondary data, and then be assessed in accordance with the principles of community-based tourism (CBT). The research results indicate that this form of public participation in the management Ambengan village is at the level of participation Degree of Tokenism (informing, consultation, and placation) of goverment. Ambengan villagers have not totally get involved, and then by developing the concept of CBT, hopefully it will be able to packaging tourism products at Ambengan village with better and in accordance with the character of the village.